Dependency of Profitability on Cash Conversion Cycle of Listed Companies: The Case of Engineering and Textile Industries in Bangladesh - Hossain, Md. Mahabbat; Rahman, Tahmina (Asian Accounting and Auditing Advancement, 2014)
For attaining better performance in manufacturing firms, working capital management plays a noteworthy role. The study analyzes the impact of the length of the cash conversion cycle on a firm’s profitability, as a performance measure. For this purpose, data of 31 manufacturing firms in the engineering and textile industries are considered which are listed on Dhaka Stock Exchanges. Relevant data have been collected from the audited financial statements published in the annual reports for the year 2011 of the concerned firms. It is suggested that the firms should try to shorten the length of the cash conversion cycle which will increase the profitability of the firms. Among three components of the cash conversion cycle, the account receivable collection period in days is more crucial for manufacturing firms. To increase sales firms should tradeoff between sales and associated risk before offering credit facilities to their customers. Analyses also reveal that listed engineering firms are more profitable than listed textile firms. The study also proves the positive association between the size of a firm and profitability.